Pengaruh Faktor Eksternal Perkumpulan Petani Pemakai Air (P3A) dalam Menunjang Keberhasilan Usahatani Padi Sawah Lahan Pasang Surut di Kabupaten Indragiri Hilir - Syafrinal, Syafrinal Syafrinal; Tabrani, Gunawan; ma’arif, Samsul (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Mahasiswa Fakultas Pertanian Universitas RiauDosen Fakultas Pertanian Universitas RiauJOM FAPERTA VOL. 6 Edisi ! Januari s/d Juni 2019 This study aims to identify the external factors of the P3A group production unit affecting the off succes agricultur bisnis of tidal rice fields in Indragiri Hilir Regency and analyze the relationship of external factors of the P3A group as a production unit to support the success of tidal rice farming in Indragiri Hilir Regency. Research has been carried out in Indragiri Hilir Regency. This study condacted from September 2016 - February 2017, using a survey method with descriptive analysis and regression and correlation. The results of this study indicate that the majority of P3A members of tidal lowland rice in Indragiri Hilir Regency have high school education down, male, productive age, have small dependents, have a narrow land area, the majority work on their own land and P3A external factors play a role in increasing the production of lowland rice in Indragiri Hilir Regency only agricultural extension workers. Agricultural extension agents have a significant relationship to the increase in productivity of tidal paddy rice in the P3A group, namely extension activities for P3A members will increase tidal rice production in Indragiri Hilir by 0.153 ton.ha-1.Keywords: Lowland rice, tides, farmer associations